PENGEMBANGAN MEDIA PEMBELAJARAN ALAT-ALAT OPTIK BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI - Ismu Sukamto; Agus Suyatna; Nengah Maharta (Jurnal Pembelajaran Fisika, 2012)
A lot of physics lab equipments are not available at scholl. The development of ICT makes it possible to create such a virtual lab equipment. The purpse of this study is to develop a medium of learning the tools of ICT-based optics. Development methods used in this study adapted the model of development which include seven procedure development, namely: analysis of needs and characteristics of students, formulating learning goals, formulating the points of matter, preparing evaluation instruments, composing media texts, expert validation, field trials, and the final products. The product have been produced in the form of instructional media optical instruments that contain material, a virtual lab which is equipped with worksheets, exercises with answer keys, and test the competence that comes with the recording of values for each correct answer. The product has been tested in accordance with the theory of quality: very attractive, very easy to use, and highly usable and declared effective as learning media optical instruments in senior high school.Key words: development research, instructional media, and optical instruments.